Estimating the Scale of Profit Shifting and Tax Revenue Losses Related to Foreign Direct Investment - Petr Jansky; Miroslav Palansky (Charles University in Prague, Institute of Economic Studies (IES), 2017)
Governments' revenues are lower when multinational enterprises avoid paying corporate income tax by shifting their profits to tax havens. In this paper, we ask which countries' tax revenues are affected most by this tax avoidance and how much. To estimate the scale of profit shifting, we start by observing that the higher is the share of foreign direct investment from tax havens, the lower is the reported rate of return on this investment. Similarly to the 2015 World Investment Report of the United Nations Conference on Trade and Development, we assume that the reported rate of return is lower due to profit shifting. Unlike the report, however, we provide illustrative country-level estimates of profit shifting related to foreign direct investment which enable us to study the distributional impact of international corporate tax abuse. We find that, on average, higher-income countries lose least and lower-income countries lose most corporate tax revenue relative to their GDP. On the basis of these estimates, we conclude that profit shifting thus deepens the existing income inequalities and the differences in government revenues between countries. Furthermore, we compare our results with three other recent studies that use different methodologies to derive country-level estimates of tax revenue losses that can be related to profit shifting. In a first such comparison made, we find that every study identifies differences across income groups, but the nature of these differences varies across the four studies.
Keywords: F21; F23; H25; 330; foreign direct investment; corporate income tax; tax avoidance; base erosion; profit shifting; inequality